Cultural industries, nation and state in the work of Renato Ortiz: A view from inside the Anglosphere - Philip Schlesinger (Ciências Sociais Unisinos)
This short essay reflects on Renato Ortiz’s work and its reception in the Anglosphere. It then discusses the author’s meeting with Ortiz in Scotland during a European-Latin American ‘encounter’ set up to discuss cultural identity and communication. Contextual changes in the past two decades are noted and the essay moves on to consider how Ortiz addressed ‘cultural industries’ in A moderna tradição brasileira. The essay concludes by relating this perspective to the contemporary debate on the ‘creative economy’.